Criminal Policy Against Account Breaking Through Automated Teller Machines (ATM) - I Nyoman Gede Sugiartha; I Made Minggu Widyantara; Ni Made Puspasutari Ujianti (Green Publisher Indonesia, 2022)
Indonesia as a state of law is obliged that the law must always be enforced, respected and obeyed by anyone without any reason for exception. In response to this, positive legal policies in Indonesia are required to be able to respond to the phenomena of crimes committed by utilizing this technology. The problems of this study are 1) What is the policy of criminal sanctions against account break-ins through Automated Teller Machines (ATMs)? 2) What is the judge's consideration in deciding the case of account burglary through Automated Teller Machines (ATMs)? The research method used is a normative legal research method, with a literature study of primary and secondary legal materials. The results of the study can be concluded that: 1) The policy of criminal sanctions against account burglary through Automated Teller Machines (ATM) in the Criminal Code, the ITE Law, the Fund Transfer Act, the Money Laundering Eradication Act. 2) The judge's consideration in deciding the case of Account Burglary through Automated Teller Machines (ATM) is that the defendant TEGUH T KHASAN has been legally proven. Aggravating things The defendant's actions can disturb the community and can cause harm to others. The mitigating factors were that the defendant admitted that he had never been convicted, the defendant was polite in court and admitted frankly his actions, the defendant felt guilty and regretful.